Collective action in East Asia : how ruling parties shape industrial policy - Noble, Gregory W. (Cornell studies in political economy., 1998)
This book offers a close look at the impact of industrial policies on collective action in East Asia - in Japan and Taiwan and, more briefly, in South Korea. Systematically comparative and based on interviews and original research in the local languages, it focuses on forms of collective action such as cartels, standardization, and research and development consortia in the consumer electronics and minimill steel industries. Gregory Noble combines detailed case studies with analyses of the political, bureaucratic, and industrial environments in which policy is crafted. He also considers how these environments have evolved in the past decade as long-ruling conservative parties have been challenged in all three countries.